2021
DOI: 10.1111/ajt.16219
|View full text |Cite
|
Sign up to set email alerts
|

Ischemia-reperfusion injury and its relationship with early allograft dysfunction in liver transplant patients

Abstract: Ischemia‐reperfusion injury (IRI) is believed to contribute to graft dysfunction after liver transplantation (LT). However, studies on IRI and the impact of early allograft dysfunction (EAD) in IRI grafts are limited. Histological IRI was graded in 506 grafts from patients who had undergone LT and classified based on IRI severity (no, minimal, mild, moderate, and severe). Of the 506 grafts, 87.4% had IRI (no: 12.6%, minimal: 38.1%, mild: 35.4%, moderate: 13.0%, and severe: 0.8%). IRI severity correlated with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
79
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 103 publications
(82 citation statements)
references
References 40 publications
2
79
1
Order By: Relevance
“…Liver ischemia-reperfusion injury (IRI) occurs when blood supply is interrupted or sharply reduced, which is the main complication of liver operation, such as hepatectomy, liver transplantation, and trauma [ 1 , 2 ]. IRI has been reported to occur in a variety of organs: heart [ 3 , 4 ], kidney [ 5 ], brain [ 6 ], and lung [ 7 ], which has high morbidity and mortality worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…Liver ischemia-reperfusion injury (IRI) occurs when blood supply is interrupted or sharply reduced, which is the main complication of liver operation, such as hepatectomy, liver transplantation, and trauma [ 1 , 2 ]. IRI has been reported to occur in a variety of organs: heart [ 3 , 4 ], kidney [ 5 ], brain [ 6 ], and lung [ 7 ], which has high morbidity and mortality worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…Warm ischemia of the liver graft is more deleterious to hepatocytes and high energy demands begin at 20⁰C of the liver core temperature [3]. It has been well reported that prolonged rWIT is associated with poor LT outcomes [4–6]. Rana et al.…”
Section: Introductionmentioning
confidence: 99%
“…Moderate/severe IRI was significantly associated with EAD occurrence ( p = 0.001). Moreover, increasing IRI severity was found to be a risk factor of a shorter 6-month graft survival ( p = 0.008) [ 79 ]. Similar conclusions were drawn by Bastos-Neves et al, after analyzing 602 liver transplantations.…”
Section: Discussionmentioning
confidence: 99%